Role of VEGFR‐1 in melanoma acquired resistance to the BRAF inhibitor vemurafenib. Issue 1 (23rd November 2019) - Atzori, Maria Grazia; Ceci, Claudia; Ruffini, Federica; Trapani, Mauro; Barbaccia, Maria Luisa; Tentori, Lucio; D'Atri, Stefania; Lacal, Pedro Miguel; Graziani, Grazia
Abstract: The vascular endothelial growth factor receptor‐1 (VEGFR‐1) is a tyrosine kinase receptor frequently expressed in melanoma. Its activation by VEGF‐A or placental growth factor (PlGF) promotes tumour cell survival, migration and invasiveness. Moreover, VEGFR‐1 stimulation contributes to pathological angiogenesis and induces recruitment of tumour‐associated macrophages. Since melanoma acquired resistance to BRAF inhibitors (BRAFi) has been associated with activation of pro‐angiogenic pathways, we have investigated VEGFR‐1 involvement in vemurafenib resistance. Results indicate that human melanoma cells rendered resistant to vemurafenib secrete greater amounts of VEGF‐A and express higher VEGFR‐1 levels compared with their BRAFi‐sensitive counterparts. Transient VEGFR‐1 silencing in susceptible melanoma cells delays resistance development, whereas in resistant cells it increases sensitivity to the BRAFi. Consistently, enforced VEGFR‐1 expression, by stable gene transfection in receptor‐negative melanoma cells, markedly reduces sensitivity to vemurafenib. Moreover, melanoma cells expressing VEGFR‐1 are more invasive than VEGFR‐1 deficient cells and receptor blockade by a specific monoclonal antibody (D16F7 mAb) reduces extracellular matrix invasion triggered by VEGF‐A and PlGF. These data suggest that VEGFR‐1 up‐regulation might contribute to melanoma progression and spreading after acquisition of a drug‐resistant phenotype. Thus, VEGFR‐1 inhibition with D16F7 mAb might be a suitable adjunct therapy for VEGFR‐1 positive tumours with acquired resistance to vemurafenib.